Effect of defibrillation on the performance of an implantable vagus nerve stimulation system - Imad Libbus; Scott R. Stubbs; Scott T. Mazar; Scott Mindrebo; Bruce H. KenKnight; Lorenzo A. DiCarlo (Bioelectronic Medicine, 2021)
Abstract Background Vagus Nerve Stimulation (VNS) delivers Autonomic Regulation Therapy (ART) for heart failure (HF), and has been associated with improvement in cardiac function and heart failure symptoms. VNS is delivered using an implantable pulse generator (IPG) and lead with electrodes placed around the cervical vagus nerve. Because HF patients may receive concomitant cardiac defibrillation therapy, testing was conducted to determine the effect of defibrillation (DF) on the VNS system. Methods DF testing was conducted on three ART IPGs (LivaNova USA, Inc.) according to international standard ISO14708-1, which evaluated whether DF had any permanent effects on the system. Each IPG was connected to a defibrillation pulse generator and subjected to a series of high-energy pulses. Results The specified series of pulses were successfully delivered to each of the three devices. All three IPGs passed factory electrical tests, and interrogation confirmed that software and data were unchanged from the pre-programmed values. No shifts in parameters or failures were observed. Conclusions Implantable VNS systems were tested for immunity to defibrillation, and were found to be unaffected by a series of high-energy defibrillation pulses. These results suggest that this VNS system can be used safely and continue to function after patients have been defibrillated.